2014
DOI: 10.3171/2014.6.focus14178
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery with and without embolization for intracranial arteriovenous malformations: a systematic review and meta-analysis

Abstract: Object The effectiveness and risk of stereotactic radiosurgery (SRS) in the management of partially embolized intracranial arteriovenous malformations (AVMs) remain controversial. The aim of this analysis was to assess current evidence regarding the efficiency and safety of SRS for AVM patients with and without prior embolization. Methods To compare SRS in patients with and without embolization, the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 50 publications
1
24
1
Order By: Relevance
“…[6-9] Radiosurgery is an accepted treatment modality for AVM located in eloquent cortex or deep brain structures. [10-14]…”
Section: Introductionmentioning
confidence: 99%
“…[6-9] Radiosurgery is an accepted treatment modality for AVM located in eloquent cortex or deep brain structures. [10-14]…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis including 10 studies with a total of 1,988 patients demonstrated that the obliteration rate was significantly lower in patients who had undergone embolization followed by SRS comparing to patients who had undergone SRS alone (41% vs 59%). The relative higher hemorrhage rate after combined treatment in this report may be partially explained by fact that nidus size and AVMs volumes were larger in the embolization group than in the nonembolized group 56 .…”
Section: Stereotactic Radiosurgery and Embolizationmentioning
confidence: 52%
“…The association is also useful for those lesions larger than 3 cm that cannot be treated by SRS alone, since the complete cure of AVMs by embolization is not the rule 3 . The concept of nidus volume reduction by endovascular treatment, making the lesion ideal for SRS, has been the only treatment option for many AVMs 3,17,20,56,63 . Although the unquestionable advantages of this association, some pitfalls have already been demonstrated in the literature.…”
Section: Stereotactic Radiosurgery and Embolizationmentioning
confidence: 99%
“…Considering that embolization before radiosurgery can decrease the rate of AVM obliteration, preradiosurgical AVM embolization should be decided prudently. 29 Patients with infratentorial AVMs have worse outcomes than those with supratentorial lesions. 30 They are more likely to present with hemorrhage, with annual rates of hemorrhage ranging from 4.4% to 11.6%, compared with all AVMs (2%-4%), and with an annual rehemorrhage rate of 34.4% for ruptured AVMs managed conservatively.…”
Section: Discussionmentioning
confidence: 99%